Street Harassment Interpretations: An Exploration of the Intersection of Gender and Race/Ethnicity, and Mediator Variables - Herrera, Jennifer (Violence against women, 2023)
How does the intersection of gender and race/ethnicity influence street harassment interpretations? What roles do attitudes and past experience play in these relationships? We examined these questions through an exploratory study of 163 Californian respondents and four hypothetical scenarios: being told to smile, being called “sexy,” hearing kissing noises, and being followed. Our findings revealed Black, Latina, and White women were more critical of these behaviors than men in their race/ethnic group. Women across all race/ethnicities interpreted the scenarios similarly with minor nuances. Street harassment views were strongly associated with prior experiences instigating street harassment and support for harassment myths.